Modern Technologies for Creating the Thin-Film Systems and Coatings 2017
DOI: 10.5772/66396
|View full text |Cite
|
Sign up to set email alerts
|

Radio Frequency Magnetron Sputter Deposition as a Tool for Surface Modification of Medical Implants

Abstract: The resent advances in radio frequency (RF)-magnetron sputtering of hydroxyapatite films are reviewed and challenges posed. The principles underlying RF-magnetron sputtering used to prepare calcium phosphate-based, mainly hydroxyapatite coatings, are discussed in this chapter. The fundamental characteristic of the RF-magnetron sputtering is an energy input into the growing film. In order to tailor the film properties, one has to adjust the energy input into the substrate depending on the desired film propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 118 publications
(182 reference statements)
0
30
0
Order By: Relevance
“…Moreover, the cytotoxic activity of the obtained material surfaces, due to toxic compound formation, was also identified [5]. Nevertheless, the osteogenic potential of amorphous and crystalline CaP coatings was demonstrated in several publications [1,4].In this paper, the results obtained from the deposited calcium phosphate layers on polyprophylene thermal sensitive polymeric substrates (with melting temperature of about 160 • C) by magnetron sputtering discharge in different experimental conditions are reported. The steady-state of the discharge and the proper parameters for the deposition of such coatings on polypropylene samples were identified by monitoring the deposition rate signal fluctuations with time.…”
mentioning
confidence: 92%
See 4 more Smart Citations
“…Moreover, the cytotoxic activity of the obtained material surfaces, due to toxic compound formation, was also identified [5]. Nevertheless, the osteogenic potential of amorphous and crystalline CaP coatings was demonstrated in several publications [1,4].In this paper, the results obtained from the deposited calcium phosphate layers on polyprophylene thermal sensitive polymeric substrates (with melting temperature of about 160 • C) by magnetron sputtering discharge in different experimental conditions are reported. The steady-state of the discharge and the proper parameters for the deposition of such coatings on polypropylene samples were identified by monitoring the deposition rate signal fluctuations with time.…”
mentioning
confidence: 92%
“…Calcium phosphate ceramic coatings represent a class of biomaterials widely used in biomedical applications, such as bone substitution and bone regeneration, due to the biocompatible, non-toxic, bioresorbable properties, as well as the similarities of their chemical composition with the inorganic component of bone structures [1]. A great biocompatible material requires a good implant-bone cell connection after the insertion of the implant in the human body to sustain new bone formation, adherence to tissues and to induce the growth of peripheral tissues [1][2][3][4][5]. In recent studies it was demonstrated that the osteointegration of the orthopedic prosthesis could be increased by covering the implant surfaces with calcium phosphate (CaP) bioactive coatings, which prove to accelerate the bone-bonding rate [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations